Pembentukan Pusat Kuliner Untuk Mendukung UMKM Bangkit di Masa Pandemi COVID-19 - Isana Arum Primasari; Wisnu Subekti (Jurnal Abdimas Madani dan Lestari (JAMALI), 2022)
"Tulasan" is one of the hamlets in Bambanglipuro District, Bantul Regency, DIY Province. The activities of the Tulasan community during the COVID-19 pandemic changed into selling ”jajanan pasar”. The new normal lifestyle forces people to be more creative in selling by utilizing social media as a medium for promoting their products so that it can make it easier for sellers to market their products. These things are a sign that the community needs assistance to survive and struggle during the COVID-19 pandemic, it is necessary to carry out community service programs in a culinary center. This location is in Tulasan, so it is called "MANTUL" which stands for Tulasan Food, it can embrace several hamlets, including Cangkring, and Jomblang. They are very close together so they can participate in selling with ”MANTUL”. The PPM programs implemented education related to health protocol in making processed food, training in making promotional by Instagram and posters, training on product packaging, and assistance in making culinary center maps. The three hamlets, culinary actors, and the community were very enthusiastic about participating in the PPM programs. The results obtained from this activity are there is an increase in people's knowledge about health procedures for food processing, increasing skills in making packaging that is in accordance with PIRT standards so that it is worthy of sale, healthy, and attractive to buyers, also increasing skills in creating content in marketing media so that can increase enthusiasm in entrepreneurship